2000
DOI: 10.1046/j.1365-8711.2000.03288.x
|View full text |Cite|
|
Sign up to set email alerts
|

X-ray analysis of the cluster 3C 129

Abstract: The cluster 3C 129 is classified as a rich cluster. An analysis of the properties of the cluster 3C 129 from ROSAT PSPC and HRI, Einstein IPC, and EXOSAT ME observations is presented. The mean temperature from a joint fit of the ROSAT PSPC and EXOSAT ME data is 5.5(±0.2) keV. The luminosity is 0.6×1044 erg s−1 in 0.2–2.4 keV and 2.7×1044 erg s−1 in 0.2–10 keV. We find a cooling flow with a rate of ∼84 M⊙ yr−1. The central gas density is 6×10−3 cm−3, and the ICM mass is 3.6×1013 M⊙. The total cluster mass is ∼5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
16
3

Year Published

2001
2001
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 18 publications
8
16
3
Order By: Relevance
“…These results are consistent with the previous findings of White et al (1997) and show that the 3C 129 cluster does not contain a strong cooling flow. They are inconsistent with the results of Leahy & Yin (2000) who claim a cooling flow of 84 M ⊙ yr −1 based on the excess luminosity over their β ‐profile fit.…”
Section: X‐ray Observationscontrasting
confidence: 99%
See 1 more Smart Citation
“…These results are consistent with the previous findings of White et al (1997) and show that the 3C 129 cluster does not contain a strong cooling flow. They are inconsistent with the results of Leahy & Yin (2000) who claim a cooling flow of 84 M ⊙ yr −1 based on the excess luminosity over their β ‐profile fit.…”
Section: X‐ray Observationscontrasting
confidence: 99%
“…These magnetic fields will have a significant impact on energy transport through the cluster, and may be dynamically important as well. Although our reanalysis of the X‐ray data does not reveal the cooling flow suggested in the past (Edge et al 1992; Leahy & Yin 2000), the field strengths derived are similar to those found in cooling flow clusters. This supports claims by Feretti et al (1999) and Clarke et al (2001) that magnetic fields are pervasive in galaxy clusters.…”
Section: Discussionsupporting
confidence: 59%
“…To explain the bending of 3C 129's jets, a velocity of 3C 129 with respect to the ICM of v gal = 500 to 3000 km s À1 is assumed by various authors (Cowie & McKee 1975;Doe et al 1995;Leahy & Yin 2000). The ICM sound velocity is c s = 1217 AE 22 km s À1 for the cluster temperature of kT ICM = 5.5 AE 0.2 keV (Leahy & Yin 2000) and a helium mass fraction of He = 0.25, so 3C 129 could have a Mach number as large as M = v/c s 2.5. The Mach cone of 3C 129 should therefore have a minimum opening angle of…”
Section: Theoretical Considerationsmentioning
confidence: 99%
“…The X-ray contours are slightly elongated in the east-west direction, suggesting that the cluster may have undergone recent merger activity. In addition, the X-ray contours are distorted near the brightest part of 3C 129; Leahy & Yin (2000) suggest that this may be caused by the radio plasma moving through the ambient cluster gas at speeds greater than the local speed of sound. The large-scale morphology of 3C 129 bends in a manner that is inconsistent with a naive tracing of its trajectory in the cluster potential.…”
mentioning
confidence: 99%
“…The radio galaxy 3C 129 is a low luminosity (FRI type) 'tailed radio galaxy' seen in projection towards the outer edge of the X-ray emission from the hot gas of a nearby cluster of galaxies (Leahy andYin, 2000, Taylor et al 2001). Since the cluster lies at low galactic latitude towards the anti-center, it has not been well studied in the optical.…”
Section: Introductionmentioning
confidence: 99%